2021
DOI: 10.1111/ppl.13549
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of GmMAPKs and functional characterization of GmMMK1 to salt stress response in soybean

Abstract: Salinity is one of the major abiotic constraints affecting the growth and yield of plants including soybean. In this context, the previous studies have documented the role of the mitogen‐activated protein kinase (MAPK) cascade in the regulation of salt signaling in model plants. However, there is not a systematic analysis of salt‐related MAPKs in soybean. Hence, in this study, we identified a total of 32 GmMAPKs via., genome‐wide reanalysis of the MAPK family using the soybean genome v4.0. Based on the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…According to the amino acid sequences, these 38 MAPKs could be clustered into four groups (Group A-D) ( Neupane et al., 2013 ). Even though a number of researches have strongly demonstrated the important roles of MAPK pathway in abiotic stress response in Arabidopsis and rice, only two MAPK kinases in G. max , GMK1/GmMPK6 (Group D) ( Im et al., 2012 ; Im et al., 2021 ) and GmMMK1 (Group B) ( Liao et al., 2021 ), have been functionally characterized to regulate salt tolerance. By association analysis of GmMKK1 sequence variations and salt tolerance in the natural soybean population, researchers showed that the sequence variation in GmMKK1 promoter was the main reason for the functional differences of GmMKK1 in the natural population in terms of the germination rates under salt treatment.…”
Section: Protein Kinases Involved In Salt-alkaline Stress Response In...mentioning
confidence: 99%
“…According to the amino acid sequences, these 38 MAPKs could be clustered into four groups (Group A-D) ( Neupane et al., 2013 ). Even though a number of researches have strongly demonstrated the important roles of MAPK pathway in abiotic stress response in Arabidopsis and rice, only two MAPK kinases in G. max , GMK1/GmMPK6 (Group D) ( Im et al., 2012 ; Im et al., 2021 ) and GmMMK1 (Group B) ( Liao et al., 2021 ), have been functionally characterized to regulate salt tolerance. By association analysis of GmMKK1 sequence variations and salt tolerance in the natural soybean population, researchers showed that the sequence variation in GmMKK1 promoter was the main reason for the functional differences of GmMKK1 in the natural population in terms of the germination rates under salt treatment.…”
Section: Protein Kinases Involved In Salt-alkaline Stress Response In...mentioning
confidence: 99%
“…The class B heat‐shock factor HSFB2b activates flavonoid biosynthesis‐related genes to promote flavonoid accumulation to relieve salt stress (Bian et al, 2020). The mitogen‐activated protein kinase (MAPK) member MMK1 negatively regulates salt tolerance by modulating root growth and salt sensitivity (Liao et al, 2021).…”
Section: Biotic and Abiotic Stress Tolerance In Soybeanmentioning
confidence: 99%
“…It has been found that plants, in response to extracellular abiotic stress, activate a complex intercellular signaling cascade that regulates physiological and biochemical changes. The Mitogen-activated protein kinase (MAPK) cascades consist of three layers of sequentially phosphorylating and activating protein kinases, including MAPK kinase kinases (MAPKKKs), MAPK kinases (MAPKKs), and MAPKs, which are highly conserved eukaryotic signaling modules acting downstream of the receptors in transducing extracellular stimuli into cellular responses (Wang et al 2022b , 2014 ; Jia et al 2022 ; Liao et al 2021 ). There are 17 MAPKs, 8 MAPKKs, and 75 MAPKKKs in the rice genome, which play crucial roles in the transduction of environmental and developmental signals, and response to various stresses (Wankhede et al 2013 ; Singh et al 2014 ; Hamel et al 2006 ; Jagodzik et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%